2021
DOI: 10.3389/fpsyg.2021.699908
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Using a Nature-Sound Mobile Application on Psychological Well-Being and Cognitive Performance Among University Students

Abstract: Many university students have been struggling with multiple challenges that may cause mental fatigue. Exposure to the natural environment is found to have restorative effects on mental fatigue, which can be explained by its benefits in physiological, psychological, and cognitive aspects. While the natural environment contains both visual and auditory elements, research on the effects of auditory elements, such as nature sounds, is underdeveloped and limited to laboratory settings. It remains unclear what are t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…Research shows that exposure to natural environments has substantial benefits for improving psychological well-being (e.g., positive effect) and cognitive performance (e.g., working memory) [ 11 , 12 , 13 , 14 , 15 , 16 ], which have the potential to improve learning performance. A prior study suggested that exposure to nature sounds (e.g., the sounds of birds, rainfall, and waves) through a mobile application in daily life can reduce university students’ mental fatigue and improve their cognitive performance [ 17 ]. However, research on whether exposure to nature sounds in daily life may influence students’ learning performance is underdeveloped.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Research shows that exposure to natural environments has substantial benefits for improving psychological well-being (e.g., positive effect) and cognitive performance (e.g., working memory) [ 11 , 12 , 13 , 14 , 15 , 16 ], which have the potential to improve learning performance. A prior study suggested that exposure to nature sounds (e.g., the sounds of birds, rainfall, and waves) through a mobile application in daily life can reduce university students’ mental fatigue and improve their cognitive performance [ 17 ]. However, research on whether exposure to nature sounds in daily life may influence students’ learning performance is underdeveloped.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Hamann and Ivtzan [ 25 ] reported that exposure to a natural environment for 30 min per day for one month could improve the positive effects (e.g., happiness, meaning in life, and mindfulness) and decrease the negative effects (e.g., distress and upset). In terms of the cognitive dimension, exposure to nature can improve attention and executive function [ 17 , 28 , 29 ] and boost the flow state [ 17 , 30 , 31 ]. For example, presenting nature scenes (e.g., Hawaiian beach) through virtual reality in an open office helped office workers to foster a flow state [ 30 ], which is a positive experiential and mental state highly related to cognitive performance occurring when people are completely immersed in their activities [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations